2007
DOI: 10.1063/1.2801405
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of laser-induced Al plasmas with cylindrical confinement

Abstract: The cylindrical confinement of laser-induced plasmas in round pipes has been investigated by optical emission spectra and fast imaging. An obvious enhancement in the emission intensity of Al atomic lines was observed when a round pipe was placed to confine the laser-induced Al plasmas. The enhancement factor for the emission intensities of the Al atomic lines was measured to be around 9 at a time delay of 12μs when the pipe diameter is 10.8mm. Assuming local thermodynamic equilibrium conditions, the plasma tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…It was shown that the confinement effect produced by the craters enhances the LIBS signal [22]. Shen et al used a series of cylindrical pipes with different diameters to confine the plasma and showed that the maximum signal enhancement factor was about 9 [23]. Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the confinement effect produced by the craters enhances the LIBS signal [22]. Shen et al used a series of cylindrical pipes with different diameters to confine the plasma and showed that the maximum signal enhancement factor was about 9 [23]. Popov et al reported the confinement effect of plasmas created in a small capped cylindrical chamber whose size was 4 mm by 4 mm, improved the limit of detection (LOD) by two to five times for different elements [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, a shock wave is produced with a plasma when a sample is ablated by a laser pulse [19]. On one hand, the plasma is confined by the magnetic field; on the other hand, the shock wave spreads out at a very high speed, and will be reflected back when encountering walls and will compress the plasma [20]. Combining these two effects, the plasma is compressed into the center, resulting in highly increased collision rates among particles within the plasma which leads to an increase in the number of atoms in high-energy states and, hence, enhanced emission spectra intensity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the spatial connement in LIBS has been studied by several groups. X. K. Shen et al 22 used a series of round pipes to conne aluminium plasmas. The maximal enhancement factor of 9 was obtained at a pipe diameter of 10.8 mm.…”
Section: -28mentioning
confidence: 99%